Stress indicators for Prochilodus lineatus (Characiformes: Prochilodontidae) breeders during passage through a fish ladder - Bido, Adriane F. (2018)
This study investigated whether fish ladder transposition is a stressful event for the streaked prochilod, Prochilodus lineatus, in a dam on the Upper Paraná River, Brazil. Bodyweight, standard length and plasma concentrations of cortisol, glucose, lactate, chloride and haematocrit were measured in 48 adult fish (male and female) that were sampled downstream and upstream of the dam and on the fish ladder. The results showed that the intense physical exertion of the fish during ladder transposition demanded high metabolic requirements and activated anaerobic pathways, but was not stressful. We recommend that physiological indicators should be used for post-construing assessments, which would improve the management of migratory fish species.